Midkine and Alk signaling in sympathetic neuron proliferation and neuroblastoma predisposition - Tobias Reiff; Leslie Huber; Marco Krämer; Olivier Delattre; Isabelle Janoueix‐Lerosey; Hermann Rohrer (2011)
Neuroblastoma (NB) is the most common extracranial solid tumor in childhood and arises from cells of the developing sympathoadrenergic lineage. Activating mutations in the gene encoding the ALK tyrosine kinase receptor predispose for NB. Here, we focus on the normal function of Alk signaling in the control of sympathetic neuron proliferation, as well as on the effects of mutant ALK. Forced expression of wild-type ALK and NB-related constitutively active ALK mutants in cultures of proliferating immature sympathetic neurons results in a strong proliferation increase, whereas Alk knockdown and pharmacological inhibition of Alk activity decrease proliferation. Alk activation upregulates NMyc and trkB and maintains Alk expression by an autoregulatory mechanism involving Hand2. The Alk-ligand Midkine (Mk) is expressed in immature sympathetic neurons and in vivo inhibition of Alk signaling by virus-mediated shRNA knockdown of Alk and Mk leads to strongly reduced sympathetic neuron proliferation. Taken together, these results demonstrate that the extent and timing of sympathetic neurogenesis is controlled by Mk/Alk signaling. The predisposition for NB caused by activating ALK mutations may thus be explained by aberrations of normal neurogenesis, i.e. elevated and sustained Alk signaling and increased NMyc expression.